Air pollution, neighborhood deprivation, and autism spectrum disorder in the Study to Explore Early Development. Issue 5 (October 2019) - McGuinn, Laura A.; Windham, Gayle C.; Messer, Lynne C.; Di, Qian; Schwartz, Joel; Croen, Lisa A.; Moody, Eric J.; Rappold, Ana G.; Richardson, David B.; Neas, Lucas M.; Gammon, Marilie D.; Schieve, Laura A.; et al.
Abstract : Background: To examine whether neighborhood deprivation modifies the association between early life air pollution exposure and autism spectrum disorder (ASD), we used resources from a multisite case–control study, the Study to Explore Early Development. Methods: Cases were 674 children with confirmed ASD born in 2003–2006; controls were 855 randomly sampled children born during the same time period and residents of the same geographic areas as cases. Air pollution was assessed by roadway proximity and particulate matter <2.5 µm (PM2.5 ) exposure during pregnancy and first year of life. To characterize neighborhood deprivation, an index was created based on eight census tract-level socioeconomic status-related parameters. The continuous index was categorized into tertiles, representing low, moderate, and high deprivation. Logistic regression was used to estimate odds ratios (ORs) and corresponding 95% confidence intervals (CIs). Results: Neighborhood deprivation modified ( P for interaction = 0.08) the association between PM2.5 exposure during the first year of life and ASD, with a stronger association for those living in high (OR = 2.42, 95% CI = 1.20, 4.86) rather than moderate (OR=1.21, 95% CI = 0.67, 2.17) or low (OR=1.46, 95% CI = 0.80, 2.65) deprivation neighborhoods. Departure from additivity or multiplicativity was not observed for roadway proximity or exposures during pregnancy. Conclusion: These results provide suggestive evidence of interaction between neighborhood deprivation and PM2.5 exposure during the first year of life in association with ASD. Abstract : Supplemental Digital Content is available in the text.